Intergenerational Effects on Fertility Behavior and Earnings Mobility in Spain - Iglesias, Feliciano Hernandez; Riboud, Michelle (The Review of Economics and Statistics, 1988)
Feliciano Hernandez Iglesias, Michelle Riboud, Intergenerational Effects on Fertility Behavior and Earnings Mobility in Spain, The Review of Economics and Statistics, Vol. 70, No. 2 (May, 1988), pp. 253-258